Serious game evaluation as a meta‐game. Issue 2 (7th June 2013) - Hall, Lynne; Jones, Susan Jane; Aylett, Ruth; Hall, Marc; Tazzyman, Sarah; Paiva, Ana; Humphries, Lynne
Abstract : Purpose: – This paper aims to briefly outline the seamless evaluation approach and its application during an evaluation of ORIENT, a serious game aimed at young adults. Design/methodology/approach: – In this paper, the authors detail a unobtrusive, embedded evaluation approach that occurs within the game context, adding value and entertainment to the player experience whilst accumulating useful data for the development team. Findings: – The key result from this study was that during the "seamless evaluation" approach, users were unaware that they had been participating in an evaluation, with instruments enhancing rather than detracting from the in‐role game experience. Practical implications: – This approach, seamless evaluation, was devised in response to player expectations, perspectives and requirements, recognising that in the evaluation of games the whole process of interaction including its evaluation must be enjoyable and fun for the user. Originality/value: – Through using seamless evaluation, the authors created an evaluation completely embedded within the "magic circle" of an in‐game experience that added value to the user experience whilst also yielding relevant results for the development team.